2020
DOI: 10.1186/s13293-020-00308-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in pharmacokinetics predict adverse drug reactions in women

Abstract: Background: Women experience adverse drug reactions, ADRs, nearly twice as often as men, yet the role of sex as a biological factor in the generation of ADRs is poorly understood. Most drugs currently in use were approved based on clinical trials conducted on men, so women may be overmedicated. We determined whether sex differences in drug pharmacokinetics, PKs, predict sex differences in ADRs. Methods: Searches of the ISI Web of Science and PubMed databases were conducted with combinations of the terms: drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
316
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(345 citation statements)
references
References 56 publications
16
316
0
13
Order By: Relevance
“…Interestingly, we found a statistically significant increase among the patients' gender, finding that females showed a higher (statistically significant) incidence (0.47 ADR/patient) as compared to males (0.26 ADR/patient). These results coincided with several sources which mention that females present ADRs more frequently than males since multiple factors like pharmacokinetic and pharmacodynamics, adipose tissue, gastrointestinal motility, enzymatic activities differences [19][20][21][22] could affect the incidence of ADRs in males and females; nevertheless, this incidence has not been reported before for ophthalmic medications.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, we found a statistically significant increase among the patients' gender, finding that females showed a higher (statistically significant) incidence (0.47 ADR/patient) as compared to males (0.26 ADR/patient). These results coincided with several sources which mention that females present ADRs more frequently than males since multiple factors like pharmacokinetic and pharmacodynamics, adipose tissue, gastrointestinal motility, enzymatic activities differences [19][20][21][22] could affect the incidence of ADRs in males and females; nevertheless, this incidence has not been reported before for ophthalmic medications.…”
Section: Discussionsupporting
confidence: 88%
“…30 Women also seem to be far more prone to over-medication, resulting in almost a doubling of adverse drug events compared with men and therefore may have a greater desire to taper off. 47 Off-label use of these medications for pain, fibromyalgia and menopausal symptoms may also contribute. 46 …”
Section: Discussionmentioning
confidence: 99%
“…There may be different factors contributing to higher ADRs in females such as the incidence of ADRs may be higher in female patients and females would have visited hospitals and consulted physicians more frequently than the males. A recent study by Zucker and Prendergast (2020) posited that females are likely to experience ADRs nearly two times that of males due to differences in their pharmacokinetic profiles 23 . On the other hand, some studies also showed that ADRs were implicated more in males as compared to females 6,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%